Edukacja dziecka ku ponadczasowym wartościom – rozważania na przykładzie współczesnej "Baśni o perle" Anny Gibasiewicz - Anna Józefowicz (Problemy Wczesnej Edukacji)
Baśń o perle (ang. Fairy tale about a pearl) by Anna Gibasiewicz (2016), is a moving story of heroes, whose fates intertwine in extraordinary circumstances, a tale of transformation and searching for the most important things in life. By its form the fairy tale refers to the folk magic tales, the mood of melancholy is similar to Andersen’s fairy tales. The story is addressed to children at the early school age. On its example, I look at the contemporary implementation of the traditional genre, which is a fairy tale and the values carried by the story. I pay attention to fairy tales, which may form the basis for educational activities with children. Analyzing the literary text of Baśń o perle (ang. Fairy tale about pearl) I refer to psychoanalytic interpretations of folk tales made by Bruno Bettelhaim and archetypal critique by Alicja Baluch. Reading fairy tales to the contemporary child still can perform a „miraculous and useful” role in his social and emotional development.